Knowledge of parents or guardians about children’s bronchial asthma. Participation of a nurse in health education of parents or guardians and a sick child - Langier, Katarzyna; Czarny-Działak, Małgorzata (Medical Studies/Studia Medyczne, 2013)
Aim of the research: To verify and assess the influence of the level of parental/guardian knowledge about a child’s bronchial asthma on the effectiveness of treatment and to define the role of health education in chronic bronchial asthma and participation of a nurse in education of parents/guardians of a child suffering from asthma. Material and methods : The method used in this thesis was a diagnostic survey. The research technique was questionnaire. The tool used in the research was a questionnaire form which consisted of 30 questions preceded by instructions. The survey was carried out among 75 parents of sick children. Results: Parental knowledge concerning children’s illness is not satisfactory, although they declare they have appropriate, good knowledge about this illness. Conclusions : Based on the analysis of the results of the research which was carried out, it is stated that because of the chronic nature of bronchial asthma it is necessary to include health education into comprehensive treatment and nursing procedures concerning children with bronchial asthma. It is also stated that participation of a well-qualified nurse in the education process is essential. It is observed that the level of parental knowledge does not depend on the length of the illness but on the effectiveness of health education. A satisfactory level of parental knowledge influences the effectiveness of treatment of bronchial asthma as an important part in prevention of exacerbations and complications.